2015
DOI: 10.1002/jclp.22164
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Potential Suicide Risk Factors Among Operation Iraqi Freedom/Operation Enduring Freedom Soldiers Returning to the Continental United States (CONUS)

Abstract: Findings highlight the utility of the IPTS in understanding precursors to suicide associated with transition from deployment, as well as treatment strategies that may reduce risk in Soldiers during reintegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…In samples of active military personnel, participants may endorse lower symptom levels due to their current military connection and less severe symptomatology (e.g., Bryan, Hernandez, Allison, & Clemans, 2013). Veterans who need inpatient treatment likely have more severe psychiatric symptoms, feel burdensome, and feel they generally do not belong due to their psychiatric symptoms (e.g., Lusk et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In samples of active military personnel, participants may endorse lower symptom levels due to their current military connection and less severe symptomatology (e.g., Bryan, Hernandez, Allison, & Clemans, 2013). Veterans who need inpatient treatment likely have more severe psychiatric symptoms, feel burdensome, and feel they generally do not belong due to their psychiatric symptoms (e.g., Lusk et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data on veteran suicides indicated that veterans exhibited a 22% higher risk of death by suicide than the general population, after controlling for age and sex (Department of Veterans Affairs [VA], 2017). This risk is likely due to combat exposure, transition out of the military, and high rates of mental and physical health concerns that veterans experience following multiple deployments (Lusk et al., 2015). Due to the increased risk of suicide in this population, research on risk factors for suicidal ideation within the Veterans Health Administration (VHA) is needed.…”
mentioning
confidence: 99%
“…Such data on factors that precipitate suicide [14][15][16][17] have guided targeted prevention efforts for groups such as middle-aged men and military and veteran populations. [18][19][20][21] Identifying factors that influence suicide risk among people with a history of cancer can identify opportunities for suicide prevention.…”
mentioning
confidence: 99%
“…Although military service can provide a sense of purpose and belonging, service members may develop high levels of PB, TB, and AC (e.g., due to combat experiences; Selby et al, 2010). Vulnerable military service members report feeling burdensome to their families; losing a sense of self, purpose, and status; and difficulty with reintegration into civilian life postdeployment (Anestis, Bryan, Cornette, & Joiner, 2009;Brenner et al, 2008;Lusk et al, 2015). Additionally, service members may feel outcast if removed from their unit (Lusk et al, 2015), especially in times of trouble or crisis.…”
mentioning
confidence: 99%